2020
DOI: 10.1016/j.dsx.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia at the time of Covid-19 pandemic

Abstract: Background: Hypoglycemia is the limiting factor in the glycemic management of diabetes, which need to be addressed critically to avoid complications. Lockdown because of new coronavirus strain (COVID-19) pandemic has further complicated the issue of hypoglycemia due to limitations in access to food, outpatient clinics, pathological services and medicines. Aim: To assess the factors associated with the risk of hypoglycemia during AprileMay 2020 lockdown in people with type 2 diabetes mellitus. Methodology: We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
1
20
0
4
Order By: Relevance
“…Sitagliptin use was significantly associated with reduction of mortality (HR, 0.44; 95% CI, 0.29 -0.66), with an improvement of COVID-19 (60% vs. 38%; P = 0.0001) as compared with patients on the standard care. Pioglitazone IL-6 expression was reduced by pioglitazone in monocytes, white adipose tissue and cardiomyocytes (Table 3 [2,[21][22][23][24]). Pioglitazone significantly reduced serum CRP levels.…”
Section: Incretin-related Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sitagliptin use was significantly associated with reduction of mortality (HR, 0.44; 95% CI, 0.29 -0.66), with an improvement of COVID-19 (60% vs. 38%; P = 0.0001) as compared with patients on the standard care. Pioglitazone IL-6 expression was reduced by pioglitazone in monocytes, white adipose tissue and cardiomyocytes (Table 3 [2,[21][22][23][24]). Pioglitazone significantly reduced serum CRP levels.…”
Section: Incretin-related Drugsmentioning
confidence: 99%
“…Sulfonylurea increases secretion of insulin, anabolic hormone, which may be beneficial for the treatment of severe infection (Table 3 [2,[21][22][23][24]). However, sulfonylurea is likely to develop hypoglycemia.…”
Section: Sulfonylureamentioning
confidence: 99%
See 2 more Smart Citations
“…Case reports from Turkey demonstrated that 3 COVID-19 patients undergoing hemodialysis who were treated with hydroxychloroquine (HCQ) developed hypoglycemia after HCQ treatment for COVID-19 [ 5 ]. Moreover, an Indian study of patients with T2D revealed that the COVID-19 lockdown has been associated with increased risk of hypoglycemia in patients with T2DM, especially those receiving sulfonylureas (SU), insulin and/or HCQ, and especially in patients with associated co-morbidities [ 6 ] . Therefore, based on the above evidence, we hypothesized that an ‘induced hypoglycemic condition’ might be an ideal stress condition to elucidate the ‘immuno-biomarkers’ for severe outcome in COVID-19.…”
mentioning
confidence: 99%